Sustainable concrete using seawater, sea-sand, and ultrafine palm oil fuel ash: Mechanical properties and durability - Dahlia Patah; Amry Dasar; Amalia Nurdin (Case Studies in Construction Materials)
Concrete production is a significant contributor to CO2 emissions and the depletion of natural resources, such as river sand and freshwater. However, these environmental impacts can be mitigated by incorporating seawater, sea-sand, and agricultural waste into concrete. Palm-oil fuel ash (POFA), an agricultural by-product from palm oil production, is often discarded in open spaces and landfills without prior processing, leading to environmental contamination. When finely ground into ultrafine POFA (UPOFA), it enhances material properties and pozzolanic reactions, making it suitable as a partial replacement for cement. After grinding with a disc mill, the UPOFA particles achieve a fineness of approximately 50 μm. However, limited research exists on the mechanical properties and durability of concrete made with seawater, sea-sand, and UPOFA. This study investigates the use of POFA as a partial cement replacement (10 %, 20 %, and 30 %) in concrete mixed with seawater and sea-sand, focusing on its role in sustainability. The study further evaluates the mechanical properties and durability of seawater sea-sand concrete incorporating UPOFA as a cement replacement. The results indicate that using seawater for mixing concrete containing 10 % UPOFA significantly enhances its mechanical properties, with the highest compressive strength of 37.95 MPa at 28 d (UP10-RS-SW), a 10.82 MPa (39.90 %) increase compared to the normal concrete (N-RS-TW), which had a compressive strength of 27.13 MPa. Additionally, the incorporation of 10 % UPOFA as a cement replacement improved compressive strength, ultrasonic pulse velocity, and corrosion resistance while reducing water absorption, porosity, and chloride penetration depth.